Nurfauzi Krisna’s Interpretation in His Performance of “Lagu Biasa” by R.A.J. Soedjasmin - M Iyyaka Bustanul Karim Karim (Repertoar, 2026)
The purpose of this study is to examine interpretations of the composition “Lagu Biasa” by R.A.J. Soedjasmin and to analyze Nurfauzi Krisna’s interpretation in his performance of the piece. The research method used is qualitative research, supported by journals, literature, and studies. The data consisted of relevant previous journal articles, expert theories, interview results, and documentation. The results of the study indicate that the song “Lagu Biasa” by R.A.J. Soedjasmin is a musical adaptation of Chairil Anwar’s poetry in the form of a serious song. This song uses an andantino tempo, varied dynamics, changes in meter, and key modulations to build emotional nuance. Nurfauzi Krisna’s interpretation demonstrates a good command of rhythm, tempo, and intonation, though dynamics and vocal timbre still need improvement.